METODE ACCELARATED SHELF LIFE TEST (ASLT) DENGAN PENDEKATAN ARRHENIUS DALAM PENDUGAAN UMUR SIMPAN SARI BUAH NANAS, PEPAYA DAN CEMPEDAK - Arif SP.MSi, Abdullah Bin (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Pineapple, papaya and cempedak are horticultural commodities that are perishable, require large space, and are usually consumed in fresh form. Based on that, technologies are required for processing them, and one alternative is juice technology. To ensure that the juice is still suitable for consumption and unspoiled, information on shelf life is necessary. Method of estimating shelf life used is ASLT (Accelarated Shelf Life Test). This research was conducted at the Laboratory of The Indonesian Center for Postharvest Agricultural Research and Development between September 2012 – January 2013. Results showed that kinetics reaction in the deterioration of vitamin C in pineapple and pineapple-Cempedak juice followed order one reaction. At storage temperature ranging between 30 °C to -5 °C pineapple-cempedak juice showed a shelf life longer than the shelf life of pineapple and pineapple-papaya juices. The estimated shelf life of pineapple-cempedak juice at a temperature of -5 °C was 197.85 days. Shelf life of pineapple-papaya juice at a temperature of -5 °C was 172.39 days. Shelf life of pineapple juice at a temperature of -5 °C was 156.85 days.